PERKEMBANGAN MORAL ANAK USIA DINI DI ERA DIGITAL: STUDI KASUS PADA PAUD MENTARI KELET - Sri Winarni; Indah Lestari; Moch. Widjanarko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Moral development in early childhood is a crucial component of character formation and is influenced by various environmental factors, including the rapid advancement of digital technology. This study aims to describe early childhood moral development in the digital era through a case study at PAUD Mentari Kelet, as well as to examine the influencing factors and the role of educational institutions in instilling moral values. A qualitative approach with a case study design was employed. The research participants included children aged 4–6 years, teachers, and parents. Data were collected through participant observation, semi-structured interviews, and documentation. The data were analyzed using thematic analysis, supported by source and method triangulation to ensure data validity. The findings indicate that the level of moral development among children at PAUD Mentari Kelet ranges from moderate to good. Variations in moral development are influenced by the intensity of digital media use and the quality of guidance provided by teachers and parents. Children who use digital media under supervision tend to demonstrate more positive moral behaviors, such as rule compliance, empathy, and cooperative skills. In contrast, unsupervised use of digital devices may lead to difficulties in self-control and reduced social interaction. The implementation of character-based digital guidance resulted in an improvement in children’s moral development, with an N-Gain score in the moderate category. It can be concluded that digital technology does not inherently have a negative impact on early childhood moral development when utilized appropriately and accompanied by consistent guidance. Therefore, collaboration between schools and parents plays a vital role in optimizing the use of digital media as a supportive tool for moral education in the digital era.